Predicting changes of the state of a bridge reinforced with concrete superstructures in view of operational changes - Ovchynnykov, Pavlo; Dubinchyk, Olha; Tiutkin, Oleksii; Kildieiev, Vitalii; Sedin, Vladimir; Bikus, Kateryna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
To solve the problem of predicting the service life of superstructures, this work proposes the basis and methodological developments of creep theory with increasing loads as well as regression analysis of the results of laboratory experiments. The main limitation in terms of reinforcement is corrosion in the concrete cracks, which was determined during laboratory experiments. Based on the results, the approximate analytical dependences concerning reinforcement corrosion depth change over time at a constant value of crack width were selected.
Keywords: bridges; superstructure; reinforced concrete; reinforcement; concrete creep; cracs; corrosion depth; most; zbrojenia; beton wzmocniony; wzmocnienie; pełzanie betonu; pęknięcie; korozja